Landau theory and giant room-temperature barocaloric effect in ⁢F3 metal trifluorides - Corrales Salazar, A. (2017)
The structural phase transitions of MF3 (M = Al, Cr, V, Fe, Ti, Sc) metal trifluorides are studied within a simple Landau theory consisting of tilts of rigid MF6 octahedra associated with soft antiferrodistortive optic modes that are coupled to long-wavelength strain generating acoustic phonons. We calculate the temperature and pressure dependence of several quantities such as the spontaneous distortions, volume expansion, and shear strains as well as T−P phase diagrams. By contrasting our model to experiments we quantify the deviations from mean-field behavior and find that the tilt fluctuations of the MF6 octahedra increase with metal cation size. We apply our model to predict giant barocaloric effects in Sc-substituted TiF3 of up to about 15JK−1kg−1 for modest hydrostatic compressions of 0.2GPa. The effect extends over a wide temperature range of over 140K (including room temperature) due to a large predicted rate, dTc/dP=723KGPa−1, which exceeds those of typical barocaloric materials. Our results suggest that open lattice frameworks such as the trifluorides are an attractive platform to search for giant barocaloric effects.